Time-resolved probing of laser-induced nanostructuring processes in liquids - Spellauge, Maximilian; Redka, David; Mo, Mianzhen; Song, Changyong; Huber, Heinz Paul; Plech, Anton (Beilstein journal of nanotechnology, 2025)
Laser synthesis and processing of colloids (LSPC) in liquids has gained widespread applications in producing nanomaterials of different classes of solids. While the technical processes in different cases of ablation, fragmentation or colloidal fusion may look macroscopically different in each application, the underlying fundamental mechanisms are always the same cascade of laser interaction with matter, non-thermal or thermal energy deposition, phase transitions, and the subsequent structure formation processes. Disentangling these mechanisms represents a veritable challenge, as ultrafast and structurally sensitive experimental methods are required. This review presents a discussion of how state-of-the-art experimental protocols using ultrafast lasers and sensitive structural probes, such as electrons or X-rays are able to address this challenge. In particular, it is possible to investigate LSPC on single objects using single probe pulses and avoid accumulation effects in a heterogeneous sample. The presented results capture structure formation with femtosecond and atomic scale resolution. Ultrafast time-resolved probing approaches are key to revealing the transient states and pathways that govern material transformation in LSPC.
Keywords: optical spectroscopy; X-ray scattering; time-resolved probing; optical imaging; single objects; pump–probe; laser processing in liquids; electron diffraction